SINKRONISASI KEWENANGAN PENGADILAN NEGERI DAN PENGADILAN AGAMA TERHADAP PENGANGKATAN ANAK BAGI ORANG ISLAM - Faturohman, Yusuf; Arimbi, Diah; Ekowati, Endang; Wahyudi, Wahyudi (Jurnal Dialektika Hukum, 2023)
Adoption of children for Muslims has different provisions when viewed from Law no. 50 of 2009 concerning the Religious Courts, where the adoption of Muslim children in religious courts. However, in reality the District Courts also do it, each has a basis, but the legal system has different provisions and of course they must be obeyed. This study aims to find out the basis on which the district court still accepts applications for adoption for Muslims and the level of synchronization of laws regarding the authority to adjudicate applications for adoption for Muslims. This study uses normative research methods, based on the results of the research showing that the district court still accepts applications for adoption submitted by people who are Muslim based on SEMA No. 3 of 2005 concerning Adoption of Children and also the best interests of the child. Whereas the Religious Courts use the basis of Law No. 50 of 2009 which legally has higher power. It is suggested that the District Court does not accept the adoption of children for the Islamic religion because according to the Law the Religious Courts have an attribution of the Law. Keywords: Adopsi, Islam